Testing young foreign language learners' reading comprehension: Exploring the effects of working memory, grade level, and reading task. (July 2021) - Brunfaut, Tineke; Kormos, Judit; Michel, Marije; Ratajczak, Michael
Extensive research has demonstrated the impact of working memory (WM) on first language (L1) reading comprehension across age groups (Peng et al., 2018), and on foreign language (FL) reading comprehension of adults and older adolescents (Linck et al., 2014). Comparatively little is known about the effect of WM on young FL readers' comprehension, and even less within testing contexts. Young FL readers are still developing their L1 reading skills and general cognitive skills (e.g., attentional regulation abilities). Completing FL reading tests might be particularly taxing on their WM, and differences in WM capacity – as well as other learner and task characteristics – might create construct-irrelevant variance in test performance. In this study, we investigate the effects of WM, grade level, and reading task on young learners' FL reading test performances. Ninety-four young English language learners (Grades 6–7) in Hungary completed the TOEFL ® Junior™ Comprehensive's reading test and a WM test battery. Our mixed-effects model predicted significantly higher comprehension accuracy among learners with higher WM capacity, and among learners in Grade 7 compared to learners in Grade 6. Reading task differences were not associated with significant comprehension accuracy differences. We discuss the implications of our findings for testing young learners' FL reading comprehension.